21 The Effect of Severe Aortic Stenosis on Aortic Haemodynamic Flow-Parameter Differences Between Bicuspid and Tri-leaflet Valve Morphology: a 4D Flow Study. (28th January 2023) - Richards, Caryl E; Parker, Alex; Alfuhied, Aseel; Debeic, Radek; Aslam, Saadia; McCann, Gerry P; Singh, Anvesha
Abstract : Introduction: Bicuspid aortic valve (BAV) is associated with earlier onset valvulo-aortopathy including aortic stenosis (AS) and aortic root dilatation than tri-leaflet aortic valves (TAV). Altered aortic haemodynamic flow patterns are linked with increased risk of BAV-associated aortopathy. 1–3 Incremental effects of AS on these are unclear. Materials and Methods: 4D flow cardiovascular magnetic resonance (4DF-CMR) was performed on 32 patients (11 BAV, 21 TAV, mean age 68 ± 10 years) with severe symptomatic AS (aortic valve area ≤ 1 cm 2 ) and 17 healthy controls (8 BAV, 9 TAV, mean age 57 ± 7 years). In-plane peak velocity and maximum wall shear stress (WSS) were evaluated from 2D analysis planes at the aortic root and distal ascending aorta (AAo) using commercial software. Peak systolic 3D volumetric velocities and vorticities averaged over the AAo (aortic root to level of pulmonary artery bifurcation) were generated using in-house Matlab code. All comparisons were adjusted for age and diastolic blood pressure. Results: In-plane peak velocities (300 ± 74 vs 176 ± 53 cm/s) and WSS at the AAo, as well as volume averaged peak velocities (434 ± 92 vs 239 ± 127 cm/s) and vorticities (152 ± 26 vs 91 ± 26 rad) were significantly higher (p < 0.01) in the overall AS cohort compared to controls. However, no significant differences were found in these variables when comparing BAV versus TAV patients with severe AS. In the control group however, in-plane peak velocities (219 ± 36 vs 137 ± 28 cm/s), AAo WSS, and 3D peak velocities (322 ± 14 vs 165 ± 39 cm/s) and vorticities (109 ± 25 vs 74 ± 11 rad) were significantly higher in the control BAV compared to TAV subjects. Discussion: 4DF-CMR demonstrated pathological aortic haemodynamic patterns in patients with severe AS compared to controls. Haemodynamic differences were also measurable in the ascending aorta of asymptomatic BAV compared to TAV controls. These differences were no longer significant in the presence of AS. Conclusion: Abnormal flow patterns in asymptomatic BAV become indistinguishable from those of TAV in the presence of severe AS, suggesting AS induces similar pathological changes in aortic haemodynamics, independent of valve morphology. References: Ward C. Clinical significance of the bicuspid aortic valve. Heart. 2000;83 (1):81–5. Borger MA, Fedak PWM, Stephens EH, Gleason TG, Girdauskas E, Ikonomidis JS, Khoynezhad A, Siu SC, Verma S, Hope MD, Cameron DE, Hammer DF, Coselli JS, Moon MR, Sundt TM, Barker AJ, Markl M, Della Corte A, Michelena HI, Elefteriades JA. The American Association for Thoracic Surgery consensus guidelines on bicuspid aortic valve-related aortopathy: full online-only version. Journal of Thoracic and Cardiovascular Surgery . 2018;156 (2):e41–e74. Singh A, Horsfield MA, Bekele S, Greenwood JP, Dawson DK, Berry C, Hogrefe K, Kelly DJ, Houston JG, Guntur Ramkumar P, Uddin A, Suzuki T, McCann GP. Aortic stiffness in aortic stenosis assessed by cardiovascular MRI: a comparison between bicuspid and tricuspid valves. European Radiology . 2019;29 (5):2340–9.